Life Cycle Assessment of Different Prefabricated Rates for Building Construction - Shaozhe Wang; Rajib Sinha (Buildings, 2021)
In recent years, Sweden has promoted prefabricated buildings supporting the increasing of prefabricated rates in buildings with precast components, in order to reduce the environmental problems caused by the construction sector. This study, focusing on the construction activities, examines how the increasing prefabricated rate could influence the environmental impacts of the construction sector. This study conducts a cradle-to-gate life cycle assessment (LCA) of a reference building with a prefabricated rate of 26% in the Stockholm Royal Seaport, and compares nine scenarios with prefabricated rates, ranging from 6% to 96%. The results indicate the water footprint decreases, but the total energy footprint and carbon footprint increase as the prefabricated rate increases. Among other impacts, terrestrial ecotoxicity shows the biggest increase with an increase of the prefabricated rate. This study reveals that material extraction is the largest influencing factor, causing a water footprint when the prefabricated rate increases. The impact changes in the energy footprint, carbon footprint, and terrestrial ecotoxicity, and are primarily determined by transport and are sensitive to transport distance and vehicle types.